Effect of Seed Extracts of Vigna unguiculta and Hordeum vulgare on Kidney Homogenate and Rat Kidney Injury Molecule-1 in Ethylene Glycol and Ammonium Chloride Induced Urolithasis in Rats - Patel, Monika; Raval, SK; Modi, RJ (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The experiment was carried out to study the therapeutic efficacy of aqueous, alcoholic, and biherbal extracts of Vigna unguiculata (VU) and Hordeum vulgare (HV) in ethylene glycol and ammonium chloride-induced urolithiasis in female Wistar rats. Rats were divided into 14 groups, each of 6 rats, except the lithiatic control group, which consisted of 8 rats. Group I and II served as lithiatic and vehicle control, respectively. In group I and III to XIV urolithiasis were induced by administration of 0.75 % (v/v) ethylene glycol and 2% (w/v) ammonium chloride along with drinking water for 28 days. Group II was given 0.5% sodium bicarbonate. After the 28th day, the rats of urolithiatic treatment Groups III to XIV were given aqueous and alcoholic seed extracts of VU and HV @ 200 mg/kg and 300 mg/kg b.wt. orally as either single extract or combination as biherbal extracts (1:1) in 0.5 % sodium bicarbonate for another 35 days using syringe and rat gavage needle. Blood samples were collected twice: on the 28th day of induction of urolithiasis and 63rd day experiment/ herbal treatment. Significantly (p <0.01) increased levels of calcium, oxalate, phosphate, and decreased levels of magnesium in the kidney homogenate were observed in the calculi induced groups as compared to the vehicle control group on 28th day. However, significantly increased rat Kidney Injury Molecule-1 (KIM-1) was observed in the calculi induced groups as compared to the vehicle control group in serum on the 28th day. Results of kidney homogenate and KIM-1 revealed that aqueous and alcoholic extracts of VU and HV possess good therapeutic efficacy against urolithiasis. The effect of biherbal alcoholic extract of the seeds at higher dose rate was much better in reducing or normalizing the values of most traits by 35 days of treatment, i.e., by 63rd day of the experiment and thus the continuation of treatment for some more days would be expected to restore the normal profile.